2021
DOI: 10.1111/jocn.15816
|View full text |Cite
|
Sign up to set email alerts
|

Occupational stressors in oncology nurses: A qualitative descriptive study

Abstract: Aim and objectives: The present study aims at exploring oncology nurses' perceptions regarding work-related stressors.Background: Oncology nurses work in an environment with a high degree of stress, which can negatively affect their health. There is limited research on work-related stressors from the oncology nurses' perspective.Design: Qualitative descriptive study.Methods: Fifty-two oncology nurses were selected purposefully from eight cancer treatment centres in different cities of Iran. Data were collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…This may be related to the higher number of oncology patients and the increased pressure on oncology nurses in recent years. When patients’ conditions worsen, they show great physical and mental pain and suffering, which becomes a vital source of stress and makes nurses depressed [ 17 , 18 ]. The findings suggest that managers must be concerned about depression among oncology nurses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be related to the higher number of oncology patients and the increased pressure on oncology nurses in recent years. When patients’ conditions worsen, they show great physical and mental pain and suffering, which becomes a vital source of stress and makes nurses depressed [ 17 , 18 ]. The findings suggest that managers must be concerned about depression among oncology nurses.…”
Section: Discussionmentioning
confidence: 99%
“…Depression, as an adverse emotional state, can seriously disturb a person’s life and work [ 15 , 16 ]. Due to the concentration of oncology patients and the high frequency of chemotherapy drug exposure, oncology nurses are constantly exposed to the refractory and negative emotions of patients and their families [ 17 , 18 ]. This particular working environment and service focus make it inevitable for oncology nurses exposed to heightened professional risks for extended periods, making them prone to depression in their work [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, many health professionals need to improve their communication skills for these processes (Slort et al, 2011), which can be stressful. (Kim & Kim, 2020; Soheili et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have reported that supportive organizational climate and leadership styles are antecedents to psychological capital (Luthans & Youssef-Morgan, 2017); however, no studies have examined factors that influence pediatric nurses’ psychological capital. Qualitatively oncology nurses frequently cite organizational support and the importance of workplace interpersonal relations in mitigating occupational stressors (Soheili et al, 2021). Furthermore, the literature supports that receiving support from colleagues can promote the quality of care delivered and increase an individual's ability to deal with stressful situations in nursing (Sodeify & Habibpour, 2020).…”
Section: Discussionmentioning
confidence: 99%